(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2022)
The article defines the concept of "video content" which is one of the main and effective components of the multimedia content of the educational process. The possibilities of using multimedia technologies at the stage of creating video lectures for students of higher educational institutions of the specialty "Construction and civil engineering" are considered. The possibilities of using multimedia technologies at the stage of creating video lectures for students of higher educational institutions of the specialty "Construction and civil engineering" are considered. The article presents statistical data on determining the role of video content in the strategy of delivering information to the user. The latest technologies for the development and editing of video content are analyzed